Significantly Elevated C-Reactive Protein Levels after Epicardial Clipping of the Left Atrial Appendage. Issue 2 (March 2018) - Verberkmoes, Niels J.; Akca, Ferdi; Vandevenne, Ann-Sofie; Jacobs, Luuk; Hamad, Mohamed A. Soliman; van Straten, Albert H.M.
Objective: Besides mechanical and anatomical changes of the left atrium, epicardial closure of the left atrial appendage has also possible homeostatic effects. The aim of this study was to assess whether epicardial clipping of the left atrial appendage has different biochemical effects compared with complete removal of the left atrial appendage. Methods: Eighty-two patients were included and underwent a totally thoracoscopic AF ablation procedure. As part of the procedure, the left atrial appendage was excluded with an epicardial clip (n = 57) or the left atrial appendage was fully amputated with an endoscopic vascular stapler (n = 25). From all patients' preprocedural and postprocedural blood pressure, electrolytes and inflammatory parameters were collected. Results: The mean age and left atrial volume index were comparable between the epicardial clip and stapler group (64 ± 8 years vs. 60 ± 9 years, P = non-significant; 44 ±15 mL/m 2 vs. 40 ± 13 mL/m 2, P = nonsignificant). Patients receiving left atrial appendage clipping had significantly elevated C-reactive protein levels compared with patients who had left atrial appendage stapling at the second, third, and fourth postoperative day (225 ± 84 mg/L vs. 149 ± 76 mg/L, P = 0.002, 244 ± 78 vs. 167 ± 76, P = 0.004, 190 ± 74vs. 105 ± 48, P < 0.001, respectively). Patients had a significant decrease in sodium levels, systolic, and diastolic blood pressure at 24 and 72 hours after left atrial appendage closure. However, this was comparable for both the left atrial appendage clipping and stapling group. Conclusions: Increased activation of the inflammatory response was observed after left atrial appendage clipping compared with left atrial appendage stapling. Furthermore, a significant decrease in blood pressure was observed after surgical removal of the left atrial appendage. Whether the inflammatory response affects the outcome of arrhythmia surgery needs to be further evaluated.